Ternary precursor material, preparation method thereof and ternary positive electrode material

By controlling the oxidation degree and particle growth of the coprecipitation reaction in stages, a ternary precursor material with high specific surface area and narrow particle size distribution was prepared, which solved the performance problems caused by the small particle size of the precursor and improved the ternary positive electrode Material uniformity and battery performance.

CN119191382APending Publication Date: 2024-12-27NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411288003.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the preparation of ternary positive electrode materials, the particle size of the precursor particles is too small, resulting in a low specific surface area, poor spherical shape and wide particle size distribution, affecting battery performance.

Method used

By adding mixed salt solution and alkali solution in four stages in the co-precipitation reaction, adjusting the nitrogen inflow and pH value, controlling the oxidation degree and particle growth, the median particle size is 2μm~3μm and specific surface area is 12m2/ ternary precursor material of g~25m2/g.

Benefits of technology

It is achieved to obtain a small particle size precursor while improving its spherical shape and particle size distribution, and improve the uniformity of the ternary positive electrode material and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191382A_ABST
    Figure CN119191382A_ABST
Patent Text Reader

Abstract

The invention provides a ternary precursor material and a preparation method thereof, and a ternary positive electrode material, the ternary precursor material comprises secondary particles formed by agglomeration of primary particles, the median particle size D50 of the secondary particles is 2 [mu] m-3 [mu] m, the specific surface area of the secondary particles is 12 m < 2 > / g-25 m < 2 > / g, the roundness of the secondary particles is 0.75-0.99, and the particle size distribution of the secondary particles satisfies # imgabs0 #. The ternary precursor material provided by the invention has the advantages of small particle size, high specific surface area, high sphericity and narrow particle size distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a ternary precursor material and a preparation method thereof, and a ternary positive electrode material. Background Art

[0002] In the preparation process of ternary positive electrode materials, the particle size and specific surface area of ​​the precursor particles will have a great influence on the performance of the positive electrode materials prepared therefrom, and small-particle precursors are usually expected to be obtained. However, in the synthesis process of small-particle precursors, there are usually problems such as low specific surface area, poor sphericity, and wide particle size distribution, and this problem will become more and more obvious as the particle size of the precursor particles gradually decreases, which can easily affect the uniformity of the ternary positive electrode material prepared from the precursor, thereby easily having an adverse effect on the performance of the battery. Summary of the invention

[0003] Based on this, the present application provides a ternary precursor material and a preparation method thereof, and a ternary positive electrode material, which can obtain a small-particle precursor while having a higher specific surface area and sphericity, as well as a narrower particle size distribution.

[0004] The first aspect of the present application provides a ternary precursor material, comprising secondary particles formed by agglomeration of primary particles, wherein the median particle size D50 of the secondary particles is 2 μm to 3 μm, and the specific surface area of ​​the secondary particles is 12 m 2 / g~25m 2 / g, the roundness of the secondary particles is 0.75-0.99, and the particle size distribution of the secondary particles satisfies: .

[0005] As for the ternary precursor material as described above, the secondary particles include an inner core and an outer layer formed on the surface of the inner core, the porosity of the inner core is 15% to 25%, and the porosity of the outer layer is 1% to 15%.

[0006] As described above, the inner core of the ternary precursor material includes a honeycomb structure formed by the interweaving of the primary particles; and / or the outer layer includes a sawtooth structure formed by the interweaving of the primary particles, the sawtooth structure includes a plurality of sawteeth, and the plurality of sawteeth extend along the radial direction of the secondary particles, from one end relatively close to the inner core to one end relatively far away from the inner core.

[0007] The ternary precursor material as described above, wherein the ratio of the diameter of the core to the diameter of the secondary particles is 40% to 65%;

[0008] And / or, the angle between any two adjacent saw teeth is 1° to 60°;

[0009] And / or, the longitudinal depth of a single one of the saw teeth is 200 nm to 600 nm.

[0010] And / or, the primary particles are in the shape of plates.

[0011] For the ternary precursor material as described above, the diameter of the core is 1 μm to 1.5 μm;

[0012] And / or, the length of the primary particles is 300 nm to 800 nm;

[0013] And / or, the width of the primary particles is 50 nm to 150 nm;

[0014] And / or, the aspect ratio of the primary particles is 2 to 10.

[0015] For the ternary precursor material as described above, at least one of the following conditions is satisfied:

[0016] (1) The ternary precursor material satisfies the following chemical formula: (Ni a Co b Mn c )M d (OH)2, where 0.8 ≤ a < 1.0, 0 < b ≤ 0.1, 0 < c ≤ 0.1, 0 ≤ d ≤ 0.005, M is a doping element and includes at least one of Zr, La, Al, Ce, W, B;

[0017] Optionally, the doping element includes Zr;

[0018] Optionally, the doping element is uniformly distributed in the ternary precursor material;

[0019] Optionally, in the ternary precursor material, the content of the doping element is 500 ppm to 5000 ppm;

[0020] (3) The tap density of the ternary precursor material is 1.5 g / cm 3 ~2 g / cm 3 .

[0021] The second aspect of the present application provides a method for preparing a ternary precursor material, including:

[0022] Under the condition of continuously introducing nitrogen and keeping the ammonia value constant, adding a mixed salt solution and a first lye to the bottom liquid in four stages respectively to successively carry out co-precipitation reactions in four stages to prepare a mixed slurry; wherein, in the four stages, the nitrogen introduction flow rate in the first stage < the nitrogen introduction flow rate in the second stage, and the nitrogen introduction flow rate in the third stage > the nitrogen introduction flow rate in the fourth stage;

[0023] After aging, separating and washing the mixed slurry, the ternary precursor material is prepared, wherein the ternary precursor material comprises secondary particles formed by agglomeration of primary particles, the median particle size D50 of the secondary particles is 2 μm to 3 μm, and the specific surface area of ​​the secondary particles is 12 m 2 / g~25m 2 / g, the roundness of the secondary particles is 0.75-0.99, and the particle size distribution of the secondary particles satisfies: .

[0024] The preparation method as described above satisfies at least one of the following conditions:

[0025] (1) The ammonia value is 1g / L~10g / L, and can be optionally 2g / L~2.5g / L;

[0026] (2) The mixed salt solution contains nickel salt, cobalt salt, manganese salt and optional salt of doped metal;

[0027] Optionally, the doping metal includes at least one of Zr, La, Al, Ce, and W, and may further be Zr;

[0028] Optionally, when the doping metal is Zr, the concentration of Zr in the mixed salt solution is 0.0012 mol / L to 0.012 mol / L;

[0029] Optionally, when the doping metal is Zr, the salt of the doping metal includes anhydrous zirconium sulfate;

[0030] (3) The concentration of the mixed salt solution is 1 mol / L to 2.5 mol / L.

[0031] The preparation method as described above satisfies at least one of the following conditions:

[0032] (1) In the four stages, the nitrogen intake amounts are respectively:

[0033] The nitrogen inlet flow rate in the first stage is 0.3m 3 / h~0.4m 3 / h;

[0034] The nitrogen inlet flow rate of the second stage is 0.5m 3 / h~0.6m 3 / h;

[0035] The nitrogen inlet flow rate of the third stage is 0.5m 3 / h~0.6m 3 / h;

[0036] The nitrogen inlet flow rate of the fourth stage is 0.1m 3 / h~0.3m 3 / h;

[0037] (2) In the four stages, the feed flow rate of the mixed salt solution increases gradually;

[0038] Optionally, in the first stage, the feed flow rate of the mixed salt solution is 0.1L / h~2L / h;

[0039] Optionally, in the second stage, the feed flow rate of the mixed salt solution is 2L / h~4L / h;

[0040] Optionally, in the third stage, the feed flow rate of the mixed salt solution is 4 L / h to 6 L / h;

[0041] Optionally, in the fourth stage, the feed flow rate of the mixed salt solution is 6L / h~8L / h;

[0042] (3) Among the four stages, the pH value of the first stage> the pH value of the second stage> the pH value of the third stage> the pH value of the fourth stage;

[0043] Optionally, 12.9≤the pH value of the first stage≤13.2;

[0044] Optionally, 12.6<the pH value of the second stage≤12.8;

[0045] Optionally, 12.4<the pH value of the third stage≤12.6;

[0046] Optionally, the pH value of the fourth stage is 11.5≤≤12.4.

[0047] (4) in the first stage, causing the mixed salt solution to overflow;

[0048] Optionally, the overflow time is 8h~10h.

[0049] The third aspect of the present application provides a ternary positive electrode material, which is prepared by the ternary precursor material of the first aspect of the present application or the ternary precursor material prepared by the preparation method of the second aspect of the present application.

[0050] The above-mentioned preparation method provided by the present application divides the coprecipitation reaction into four stages in succession, which is conducive to improving the uniformity of the precursor particles. Among them, by adjusting the amount of nitrogen introduced in each stage, the oxygen content in each stage can be regulated and controlled respectively, and the nitrogen introduced flow rate in the first stage is made less than the nitrogen introduced flow rate in the second stage, which can make the early stage nucleate with a low degree of oxidation, reduce the generation of particles with too small particle size due to excessive oxidation, and also reduce particle agglomeration, which is conducive to the improvement of particle sphericity and the reduction of particle size distribution. And making the nitrogen introduced flow rate in the third stage > the nitrogen introduced flow rate in the fourth stage, it can make the later stage grow with a high degree of oxidation, which is conducive to the improvement of the specific surface area of ​​the precursor particles. At the same time, keeping the ammonia value constant in the four stages can also be conducive to the improvement of specific surface area to a certain extent. Thus, the ternary precursor material obtained by the preparation method of the present application, while obtaining a small particle size, also has a higher specific surface area and sphericity, and a narrower particle size distribution. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] FIG. 1 is a surface morphology of the ternary precursor material prepared in Example 1.

[0052] FIG2 is a cross-sectional view of the ternary precursor material prepared in Example 1.

[0053] FIG3 is a cross-sectional EDS-mapping spectrum of the ternary precursor material prepared in Example.

[0054] FIG. 4 is a surface morphology of the ternary precursor material prepared in Example 5.

[0055] FIG5 is a surface morphology of the ternary positive electrode material prepared in Comparative Example 1.

[0056] FIG6 is a cross-sectional view of the ternary positive electrode material prepared in Comparative Example 1.

[0057] FIG. 7 is a surface morphology of the ternary positive electrode material prepared in Comparative Example 2.

[0058] FIG8 is a cross-sectional view of the ternary positive electrode material prepared in Comparative Example 2.

[0059] FIG. 9 is a surface morphology of the ternary precursor material prepared in Example 6.

[0060] FIG10 is a surface morphology of the ternary precursor material prepared in Example 9. DETAILED DESCRIPTION

[0061] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0062] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0063] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" are inclusive of the number, and the meaning of "multiple" in "one or more" is more than two.

[0064] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​within the numerical interval is considered to be continuous and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to integers within the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0065] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.

[0066] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0067] During the research, the inventors found that the particle size of the precursor will have a great influence on the performance of the ternary positive electrode material prepared therefrom. Among them, the smaller particle size can make the active ions diffuse and transfer in a shorter channel, match the appropriate large specific surface area, and make the active ion deintercalation more active, which can play a positive role in the application of high-capacity and high-rate batteries. However, in the preparation process of the precursor, the smaller the particle size of the precursor particles is, the higher the surface energy of the particles is, the more serious the adhesion of the crystal nuclei is, and the more likely it is to agglomerate, resulting in irregular morphology of the finished precursor, poor sphericity of the particles, low specific surface area, and wide particle size distribution. Therefore, it is very difficult to prepare precursor particles with a small particle size (such as a particle size ≤3μm), a narrow particle size distribution and a large specific surface area. Based on this, the inventors proposed the following technical solution of this application.

[0068] In a first aspect, the present application provides a method for preparing a ternary precursor material, which may include the following steps S1-S2:

[0069] S1: Under the condition of continuously introducing nitrogen and maintaining a certain ammonia value, a mixed salt solution and a first alkali solution are added to the base liquid in four stages to carry out four stages of co-precipitation reaction in succession to prepare a mixed slurry; wherein, in the four stages, the nitrogen introduction flow rate of the first stage is less than the nitrogen introduction flow rate of the second stage, and the nitrogen introduction flow rate of the third stage is greater than the nitrogen introduction flow rate of the fourth stage.

[0070] S2: After aging, separating and washing the mixed slurry, the ternary precursor material is prepared, wherein the ternary precursor material includes secondary particles formed by agglomeration of primary particles, the median particle size D50 of the secondary particles is 2 μm to 3 μm, and the specific surface area of ​​the secondary particles is 12 m 2 / g~25m 2 / g, the roundness of the secondary particles is 0.75-0.99, and the particle size distribution of the secondary particles satisfies: .

[0071] It should be noted that the "ammonia value" mentioned in this application refers to the amount (g) of ammonia (NH3) dissolved in one liter of solution.

[0072] The above-mentioned preparation method provided by the present application divides the coprecipitation reaction into four stages in succession, which is beneficial to improve the uniformity of the precursor particles. Among them, by adjusting the amount of nitrogen introduced in each stage, the oxygen content in each stage can be regulated and controlled respectively, and the nitrogen introduced flow rate in the first stage is made less than the nitrogen introduced flow rate in the second stage, which can make the early stage nucleate with low oxidation degree, reduce the generation of particles with too small particle size due to excessive oxidation, and also reduce particle agglomeration, which is beneficial to the improvement of particle sphericity and the reduction of particle size distribution. And making the nitrogen introduced flow rate in the third stage > the nitrogen introduced flow rate in the fourth stage, it can make the later stage grow with high oxidation degree, which is beneficial to the improvement of the specific surface area of ​​the precursor particles. At the same time, keeping the ammonia value constant in the four stages can also be beneficial to the improvement of specific surface area to a certain extent.

[0073] The present invention adopts a method of regulating the degree of oxidation by regulating the nitrogen inlet flow rate. Compared with the method of directly oxidizing by passing air, the oxygen content is easier to control and over-oxidation is less likely to occur, which is beneficial to the improvement of particle sphericity and specific surface area, and also beneficial to the reduction of particle size distribution. Finally, the median particle size D50 can be 2μm~3μm and the specific surface area can be 12m 2 / g~25m 2 / g, roundness is 0.75~0.99 and particle size distribution meets Ternary precursor materials.

[0074] In some embodiments, the ammonia value in step S1 is 1 g / L to 10 g / L, and can be 2 g / L to 2.5 g / L. For example, the ammonia value can be 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L or within the range of any of the above values. This is beneficial to increase the specific surface area of ​​the particles.

[0075] In some embodiments, in the four stages, the coprecipitation temperature of each stage is independently 40° C. to 70° C. For example, the coprecipitation temperature of each stage can be independently 40° C., 45° C., 50° C., 55° C., 60° C., 65° C., 70° C. or within the range of any of the above values.

[0076] In some embodiments, the time of the coprecipitation reaction in the first stage is 15 h to 20 h. For example, the time can be 15 h, 16 h, 17 h, 18 h, 19 h, 20 h or within the range of any of the above values.

[0077] In some embodiments, the coprecipitation reaction time of the second stage is 5 h to 10 h. For example, the time can be 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or within the range of any of the above values.

[0078] In some embodiments, the coprecipitation reaction time of the third stage is 1 h to 5 h. For example, the time can be 1 h, 2 h, 3 h, 4 h, 5 h or any range thereof.

[0079] In some embodiments, the coprecipitation reaction time of the fourth stage is 30 h to 60 h. For example, the time can be 30 h, 35 h, 40 h, 45 h, 50 h, 55 h, 60 h or any range thereof.

[0080] In some embodiments, the mixed salt solution comprises a nickel salt, a cobalt salt, a manganese salt, and optionally a salt of a doping metal.

[0081] In this way, compared with the doping method of doping metals during the preparation of ternary positive electrode materials, the present application performs doping in the precursor, which can more accurately control the doping amount of the doped metal, facilitate the atomic-level doping of the doped metal, and enable the doped metal to be evenly distributed in the ternary precursor material and the ternary positive electrode material prepared thereby.

[0082] In some embodiments, the nickel salt includes nickel sulfate and / or nickel nitrate.

[0083] In some embodiments, the cobalt salt includes cobalt sulfate and / or cobalt nitrate.

[0084] In some embodiments, the manganese salt comprises manganese sulfate and / or manganese nitrate.

[0085] In some embodiments, the metal-doped salt includes a metal-doped sulfate and / or a metal-doped nitrate.

[0086] In some embodiments, the doped metal includes at least one of Zr, La, Al, Ce, and W, and may be Zr. Doping with metals, especially Zr, is beneficial to reducing the surface energy of the particles, alleviating the crystal nucleus agglomeration phenomenon, and effectively improving the sphericity of the particles.

[0087] In some embodiments, when the doping metal is Zr, the concentration of Zr in the mixed salt solution is 0.0012 mol / L~0.012 mol / L. By regulating the concentration of zirconium in the mixed salt solution, it is possible to achieve quantitative doping of Zr in the ternary precursor material. Since the doping amount of the Zr element will have a certain effect on the capacity and cycle stability, too high a doping amount will lead to a decrease in capacity, and too low a doping amount may cause the structural stability of the positive electrode active material to decrease. Therefore, the quantitative doping amount of the Zr element can not only make the positive electrode active material have a higher capacity but also make it have a higher structural stability, effectively extending the cycle life of the battery.

[0088] In some embodiments, when the doping metal is Zr, the salt of the doping metal includes anhydrous zirconium sulfate.

[0089] When the mixed salt solution contains anhydrous zirconium sulfate, nickel salt, cobalt salt and manganese salt, it is equivalent to dissolving anhydrous zirconium sulfate in a nickel-cobalt-manganese sulfate solution. Compared with the mixed salt solution containing nickel salt, cobalt salt and manganese salt, but using anhydrous zirconium sulfate alone as an additive solution, dissolving anhydrous zirconium sulfate in a nickel-cobalt-manganese sulfate solution can inhibit the formation of precipitation, and even when the concentration of anhydrous zirconium sulfate is low, no white precipitation will appear when the solution is left for a long time. This is conducive to improving the atomic utilization rate of Zr, reducing costs and avoiding waste; and it can minimize the deviation of the actual doping amount of Zr from the design value, reducing the adverse effects on the performance of the ternary precursor material caused by this.

[0090] In some embodiments, the concentration of the mixed salt solution is 1 mol / L to 2.5 mol / L. For example, the concentration may be 1 mol / L, 1.3 mol / L, 1.5 mol / L, 1.7 mol / L, 2 mol / L, 2.3 mol / L, 2.5 mol / L or within the range of any of the above values. When the mixed salt concentration is within the above range, the number of crystal nuclei formed by the primary particles is more appropriate, which can avoid the problem of the internal structure of the positive electrode material precursor particles being not compact enough and the roundness being poor as much as possible, and can also reduce the risk of the positive electrode material precursor particles being easily agglomerated.

[0091] In some embodiments, the nitrogen inlet flow rate of the first stage is 0.3m 3 / h~0.4m 3 / h. For example, the nitrogen flow rate in the first stage can be 0.3m 3 / h, 0.32m 3 / h, 0.34m 3 / h, 0.36m 3 / h, 0.38m 3 / h, 0.4m 3 / h or any of the above values ​​within the range.

[0092] In some embodiments, the nitrogen inlet flow rate of the second stage is 0.5m 3 / h~0.6m 3 / h. For example, the nitrogen flow rate in the second stage can be 0.5m 3 / h, 0.52m 3 / h, 0.54m 3 / h, 0.56m 3 / h, 0.58m 3 / h, 0.6m 3 / h or any of the above values ​​within the range.

[0093] In some embodiments, the nitrogen inlet flow rate of the third stage is 0.5m 3 / h~0.6m 3 / h. For example, the nitrogen inlet flow rate in the third stage can be 0.5m 3 / h, 0.51m 3 / h, 0.53m 3 / h, 0.55m 3 / h, 0.57m 3 / h, 0.6m 3 / h or any of the above values ​​within the range.

[0094] In some embodiments, the nitrogen inlet flow rate of the fourth stage is 0.1m 3 / h~0.3m 3 / h. For example, the nitrogen flow rate in the fourth stage can be 0.1m 3 / h, 0.12m 3 / h, 0.14m 3 / h, 0.16m 3 / h, 0.18m 3 / h, 0.2m 3 / h, 0.22m 3 / h, 0.24m 3 / h, 0.26m 3 / h, 0.28m 3 / h, 0.3m 3 / h or any of the above values ​​within the range.

[0095] The nitrogen flow rate at each stage is regulated to the above-mentioned respective ranges. On the one hand, it is conducive to forming a loose honeycomb structure inside and a dense zigzag structure on the surface in the ternary precursor material. On the other hand, when the metal-doped salt includes zirconium sulfate, that is, when the mixed salt solution contains zirconium sulfate, zirconium sulfate is easily oxidized and easily nucleated alone, so it is difficult to co-precipitate with nickel, cobalt, and manganese. If the method of directly oxidizing by air is adopted, the degree of oxidation is difficult to control, which easily leads to too wide particle size distribution and the phenomenon of large and small balls. The present application adopts the method of regulating the degree of oxidation by regulating the nitrogen flow rate, and the nitrogen flow rate at each stage is regulated to the above-mentioned respective ranges, so that the oxygen content variation range during the reaction at each stage can be small, and the nucleation of zirconium sulfate alone can be avoided as much as possible, which is conducive to improving the uniformity of particle size distribution.

[0096] In some embodiments, in the four stages, the feed flow rate of the mixed salt solution increases gradually (ie, a gradient increasing flow process).

[0097] It should be noted that the "gradient increase" mentioned in the present application means that in the four stages, the feed flow rate of the mixed salt solution in the latter stage is w2, and the feed flow rate of the mixed salt solution in the previous stage adjacent to it is w1. >0.

[0098] In this way, the reactor is started when the material flow rate is low, the number of free transition metal ions in the reactor is reduced, the supersaturation of the solution is reduced, the rate of nucleation formation is inhibited, the number of early nuclei is reduced to reduce agglomeration, and the sphericity of the ternary precursor material is improved.

[0099] In some embodiments, in the first stage, the feed flow rate of the mixed salt solution is 0.1 L / h to 2 L / h. For example, the feed flow rate can be 0.1 L / h, 0.3 L / h, 0.5 L / h, 0.7 L / h, 1 L / h, 1.3 L / h, 1.5 L / h, 1.7 L / h, 2 L / h or within the range of any of the above values.

[0100] In some embodiments, in the second stage, the feed flow rate of the mixed salt solution is 2 L / h to 4 L / h. For example, the feed flow rate can be 2 L / h, 2.3 L / h, 2.5 L / h, 2.7 L / h, 3 L / h, 3.3 L / h, 3.5 L / h, 3.7 L / h, 4 L / h or within the range of any of the above values.

[0101] In some embodiments, in the third stage, the feed flow rate of the mixed salt solution is 4 L / h to 6 L / h. For example, the feed flow rate can be 4 L / h, 4.3 L / h, 4.5 L / h, 4.7 L / h, 5 L / h, 5.3 L / h, 5.5 L / h, 5.7 L / h, 6 L / h or within the range of any of the above values.

[0102] In some embodiments, in the fourth stage, the feed flow rate of the mixed salt solution is 6 L / h to 8 L / h. For example, the feed flow rate can be 6 L / h, 6.3 L / h, 6.5 L / h, 6.7 L / h, 7 L / h, 7.3 L / h, 7.5 L / h, 7.7 L / h, 8 L / h or within the range of any of the above values.

[0103] The feed flow rate of the mixed salt solution in each stage is regulated to the above respective ranges, which, on the one hand, is conducive to improving the sphericity of the ternary precursor material; on the other hand, it is conducive to forming a loose internal honeycomb structure and a dense surface serrated structure in the ternary precursor material.

[0104] In some embodiments, among the four stages, the pH value of the first stage>the pH value of the second stage>the pH value of the third stage>the pH value of the fourth stage. In this way, it is beneficial to form a loose honeycomb structure inside and a dense zigzag structure on the surface in the ternary precursor material.

[0105] It can be understood that the first alkali solution in step S1 can adjust the pH value of each stage. Optionally, the first alkali solution can be a sodium hydroxide solution.

[0106] In some embodiments, 12.9≤the pH value of the first stage≤13.2. For example, the pH value of the first stage can be 12.9, 13, 13.1, 13.2 or within the range of any of the above values. The higher pH in the first stage can reduce the supersaturation of the reaction material, thereby increasing the rate at which the primary particles form crystal nuclei, reducing their growth rate, allowing the crystals to grow slowly, and avoiding excessive nucleation leading to a long reaction time.

[0107] In some embodiments, 12.6 < pH value of the second stage ≤ 12.8. For example, the pH value of the second stage can be 12.7, 12.8 or within the range of any of the above values. Compared with the first stage, the feed flow rate in the second stage system is increased and the pH value is slightly reduced, which can increase the growth rate of the crystal to a certain extent and reduce the number of gaps between the primary particles, so that the crystal part grown in this stage has a lower porosity than the crystal part grown in the first stage.

[0108] In some embodiments, 12.4 < the pH value of the third stage ≤ 12.6. For example, the pH value of the third stage can be 12.5, 12.6, or within the range of any of the above values. In the third stage system, the feed flow rate is higher, and the pH value is further reduced, the growth rate of the crystal is further improved, and the number of gaps between the primary particles is smaller, so that the porosity of the crystal part grown in this stage is further reduced, and the structure is more compact.

[0109] In some embodiments, 11.5≤the pH value of the fourth stage≤12.4. For example, the pH value of the fourth stage can be 11.5, 11.6, 11.7, 11.8, 11.9, 12, 12.1, 12.2, 12.3, 12.4 or within the range of any of the above values. The flow rate in the fourth stage reaction system is higher, the pH value is lower, and the growth rate of the ternary cathode material precursor is faster than that in the third stage, so that the gaps between the primary particles are further reduced, and the primary particles in the crystal part generated in this stage have a dense zigzag structure.

[0110] In some embodiments, in the first stage, the mixed salt solution is overflowed.

[0111] This is beneficial to reduce the number of free transition metal ions, reduce the supersaturation of the solution, inhibit the rate of crystal nucleation, reduce the number of early crystal nuclei to reduce early agglomeration, and improve sphericity.

[0112] In some embodiments, the overflow time is 8h to 10h. For example, the overflow time can be 8h, 9h, 10h or within the range of any of the above values. When the overflow time is within this range, the number of generated nuclei is moderate and the reaction time is moderate; if the overflow time is too short, it is easy to cause serious agglomeration of the precursor in the later stage and poor sphericity; if the overflow time is too long, it is easy to cause material waste and low solid content in the later stage.

[0113] In some embodiments, the method for preparing the base liquid may include the following steps: adding ammonia water and a second alkali solution to water at a preset temperature, and continuously introducing nitrogen gas to prepare the base liquid.

[0114] It is understood that the second alkali solution can adjust the pH value of the base solution. Optionally, the second alkali solution can be a sodium hydroxide solution.

[0115] In some embodiments, the preset temperature is 40°C to 70°C.

[0116] In some embodiments, the pH value of the base solution is 12-13.5.

[0117] In some embodiments, the nitrogen gas flow rate is 0.1m 3 / h~1m 3 / h.

[0118] In the second aspect, the present application provides a ternary precursor material, which can be prepared by the preparation method of the first aspect of the present application, the ternary precursor material comprises secondary particles formed by agglomeration of primary particles, the median particle size D50 of the secondary particles is 2 μm to 3 μm, and the specific surface area of ​​the secondary particles is 12 m 2 / g~25m 2 / g, the roundness of the secondary particles is 0.75-0.99, and the particle size distribution of the secondary particles satisfies: .

[0119] The median particle size of the traditional ternary precursor secondary particles is usually greater than 3.5 μm, and the larger particles usually have a smaller specific surface area, which is not conducive to the lithium ions entering the precursor during the sintering process, which is not conducive to the capacity of the positive electrode active material. The median particle size of the ternary precursor material provided in this application is smaller, and the smaller median particle size can not only make the ternary positive electrode material prepared therefrom have a shorter active ion diffusion channel, so that the active ions can be diffused and transferred in the shorter channel; and the smaller median particle size matches the appropriate large specific surface area, and can also make the active ions in the prepared ternary positive electrode material more active, which is conducive to the improvement of battery capacity and rate performance; at the same time, the precursor material with a smaller median particle size, higher roundness and narrower particle size distribution can also make the prepared ternary positive electrode material less likely to have new crystal planes during the cyclic charge and discharge process, thereby reducing the occurrence of side reactions between the electrolyte and the interface and improving the cycle performance of the battery.

[0120] In some embodiments, the median particle size D50 of the secondary particles can be 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm or within a range of any of the above values. The smaller median particle size of the secondary particles enables the active ions to diffuse and transfer in a shorter channel.

[0121] In some embodiments, the specific surface area of ​​the secondary particles may be 12 m 2 / g,14m 2 / g,15m 2 / g,17m 2 / g,19m 2 / g,20m 2 / g,21m 2 / g,23m 2 / g,25m 2 / g or within the range of any of the above values. Optionally, the specific surface area of ​​the secondary particles is 15m 2 / g~25m 2 / g. The appropriate large specific surface area can make the active ions more active in embedding and de-embedding, which is beneficial to the improvement of battery capacity and rate performance.

[0122] In some embodiments, the roundness of the secondary particles is 0.75 to 0.99. For example, the roundness of the secondary particles can be 0.75, 0.77, 0.79, 0.81, 0.83, 0.85, 0.87, 0.89, 0.91, 0.93, 0.95, 0.97, 0.99 or within the range of any of the above values. Higher sphericity is conducive to the improvement of specific surface area and the reduction of particle size distribution. Optionally, the roundness of the secondary particles is 0.85 to 0.99.

[0123] In some embodiments, the particle size distribution of the secondary particles satisfies: . For example, (D90-D10) / D50 can be 0.5, 0.7, 0.9, 1, 1.1, 1.3, 1.5, 1.6, 1.7, 1.75 or any range thereof. A narrow particle size distribution is conducive to improving the uniformity of the particles, thereby improving the performance of the ternary cathode material and the capacity of the battery. Optionally, the particle size distribution of the secondary particles satisfies: It can be understood that the "roundness" mentioned in this application refers to sphericity.

[0124] It should be noted that the ternary positive electrode material prepared using the ternary precursor material of the present application can basically inherit all the morphological characteristics of the ternary precursor material, such as the porosity of the inner core and the outer layer, the honeycomb structure of the inner core, the serrated structure of the outer layer, etc.

[0125] In some embodiments, the secondary particles include an inner core and an outer layer formed on the surface of the inner core, the inner core has a porosity of 15% to 25%, and the outer layer has a porosity of 1% to 15%. For example, the inner core may have a porosity of 15%, 20%, 25%, or any range thereof. The outer layer may have a porosity of 1%, 5%, 10%, 15%, or any range thereof.

[0126] In this way, on the one hand, it is conducive to further shortening the diffusion path of active ions, making it easier for active ions to penetrate into the interior of the ternary precursor during the sintering process, and the number of combined active ions is larger and more uniform, which is conducive to further significantly improving the cycle performance and capacity of the ternary positive electrode material. On the other hand, it is conducive to further absorption and storage of active ions in the positive electrode material, alleviating the volume expansion during the charge and discharge process.

[0127] In some embodiments, the porosity of the secondary particles gradually decreases from the inner core to the outer layer.

[0128] In some embodiments, the inner core comprises a honeycomb structure formed by the primary particles intertwining with each other.

[0129] In some embodiments, the outer layer includes a sawtooth structure formed by the primary particles interweaving with each other, and the sawtooth structure includes a plurality of sawteeth, and the plurality of sawteeth extend along the radial direction of the secondary particle from an end relatively close to the inner core to an end relatively far from the inner core.

[0130] The porosity decreases gradually from the inner core to the outer layer. The inner core is a loose and porous honeycomb structure, which is conducive to the absorption and storage of active ions and alleviates the volume expansion during charging and discharging. The outer layer includes a serrated structure, which can shorten the diffusion path of active ions when preparing ternary positive electrode materials, making it easier for active ions to penetrate into the interior of the ternary precursor and combining more and more active ions more evenly, which is beneficial to significantly improve the cycle performance and capacity of the active ternary positive electrode materials.

[0131] It can be understood that the “active ions” mentioned in the present application include lithium ions.

[0132] In some embodiments, the diameter of the core is 1 μm to 1.5 μm. For example, the diameter of the core can be 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm or within the range of any of the above values. If the core diameter is relatively small, the porosity inside the ternary precursor will be low, which is not conducive to the storage and transmission of active ions in the positive electrode active material prepared therefrom; if the core diameter is relatively large, the inside of the ternary precursor will be too loose, which is not conducive to subsequent sintering.

[0133] In some embodiments, the ratio of the diameter of the core to the diameter of the secondary particle is 40% to 65%. For example, the diameter ratio can be 40%, 45%, 50%, 55%, 60%, 65% or any range thereof. This facilitates further absorption and storage of active ions, thereby alleviating volume expansion during charge and discharge.

[0134] In some embodiments, the angle between any two adjacent saw teeth is 1° to 60°. For example, the angle may be 1°, 5°, 10°, 15°, 20°, 25°, 30°, 35°, 40°, 45°, 50°, 55°, 60° or within the range of any of the above values. If the angle is relatively large, the stacking of the primary particles will be too loose, which is not conducive to the cycle performance of the ternary positive electrode material prepared therefrom; if the angle is relatively small, the stacking of the primary particles will be too dense, the specific surface area will be too small, which is not conducive to the diffusion of the active substance.

[0135] In some embodiments, the longitudinal depth of a single sawtooth is 200 nm to 600 nm. For example, the longitudinal depth can be 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, or any range thereof. If the longitudinal depth is relatively large, a ball-splitting phenomenon may occur; if the longitudinal depth is relatively small, it is not conducive to the diffusion of the active substance.

[0136] This is not only beneficial to the diffusion of active ions, but also less likely to cause ball splitting during the precursor preparation process. At the same time, in the process of preparing ternary positive electrode materials, structural collapse is less likely to occur, which is beneficial to long-term circulation.

[0137] It should be noted that the "longitudinal depth of a single saw tooth" mentioned in the present application refers to the length of a single saw tooth, that is, the total length of a single saw tooth extending from one end relatively close to the core to one end relatively far from the core.

[0138] In some embodiments, the primary particles are in the shape of laths.

[0139] In some embodiments, the length of the primary particle is 300 nm to 800 nm. For example, the length of the primary particle can be 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm or any range thereof.

[0140] In some embodiments, the width of the primary particle is 50 nm to 150 nm. For example, the width of the primary particle can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm or any range thereof.

[0141] When the length and width of the primary particles are within the above range, the primary particles can form a higher aspect ratio and are not easy to break, which is beneficial to increase the specific surface area of ​​the ternary positive electrode material precursor and make lithium ions easier to embed during the sintering process, thereby further increasing the capacity of the positive electrode active material.

[0142] In some embodiments, the aspect ratio of the primary particles is 2 to 10. For example, the aspect ratio of the primary particles can be 2, 3, 4, 5, 6, 7, 8, 9, 10 or within the range of any of the above values. The aspect ratio within this range is conducive to increasing the specific surface area of ​​the ternary cathode material precursor.

[0143] It should be noted that the “aspect ratio of primary particles” mentioned in the present application refers to the ratio between the length and width of the primary particles.

[0144] In some embodiments, the ternary precursor material satisfies the following chemical formula: (Ni a Co b Mn c )M d(OH)2, where 0.8 ≤ a < 1.0, 0 < b ≤ 0.1, 0 < c ≤ 0.1, 0 ≤ d ≤ 0.005, M is a doping element and includes at least one of Zr, La, Al, Ce, W, and B. The doping element in the precursor is beneficial to improving the cycling performance of the ternary cathode material prepared from the precursor material, and can effectively avoid particle breakage and cracking caused by excessive local stress.

[0145] In some embodiments, the doping element includes Zr. After the Zr element enters the precursor through bulk doping, it can reduce the surface energy of the primary particles, alleviate the nucleation agglomeration phenomenon, improve the sphericity, and reduce the particle size distribution. At the same time, the 4+ ionic radius of Zr is slightly larger than that of nickel cobalt manganese, and the Zr 4+ incorporated into the unit cell will increase the crystal layer spacing and expand the active ion transport channels.

[0146] In some embodiments, the doping element is uniformly distributed in the ternary precursor material. The uniform distribution of the doping element in the precursor is beneficial to further improving the cycling performance of the ternary cathode material prepared therefrom, and can effectively avoid particle breakage and cracking caused by excessive local stress.

[0147] It should be noted that the "uniform distribution" described in this application means that the presence of the doping element can be detected at any position in the ternary precursor material.

[0148] In some embodiments, in the ternary precursor material, the content of the doping element is 500 ppm to 5000 ppm. For example, the content of the doping element can be 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm or within the range composed of any of the above values. In this way, it is beneficial to further improve the sphericity and reduce the particle size distribution, and further expand the transport channels of active ions.

[0149] In some embodiments, the tap density of the ternary precursor material is 1.5 g / cm 3 ~2 g / cm 3 . For example, the tap density can be 1.5 g / cm 3 , 1.6 g / cm 3 , 1.7 g / cm 3 , 1.8 g / cm 3 , 1.9 g / cm 3 , 2 g / cm 3 or within the range composed of any of the above values. If the tap density is relatively low, it is not conducive to the improvement of the energy density after subsequent sintering into the ternary cathode material; if the tap density is relatively high, the specific surface area of the ternary precursor is usually low, which is not conducive to the insertion and extraction of active substances.

[0150] In a third aspect, the present application provides a ternary positive electrode material, which can be prepared by the ternary precursor material of the first aspect of the present application or the ternary precursor material prepared by the preparation method of the second aspect of the present application.

[0151] In a fourth aspect, the present application provides a battery comprising the ternary positive electrode material of the third aspect of the present application.

[0152] Example

[0153] The following are specific examples, which more specifically describe the contents disclosed in this application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0154] Example 1

[0155] (1) Nickel sulfate, cobalt sulfate, manganese sulfate, and anhydrous zirconium sulfate were added to deionized water to prepare a mixed salt solution with a total ion concentration of 1.5 mol / L, a molar ratio of metal ions Ni:Co:Mn of 93:3.5:3.5, and a Zr concentration of 0.0073 mol / L; ammonia water and deionized water were prepared into a 9.8 mol / L complexing agent solution; sodium hydroxide was prepared into an 11 mol / L alkaline solution.

[0156] (2) Fill a 100L clean reactor with deionized water, maintain the water temperature in the reactor at 65°C, and start stirring at a speed of 600 rpm; pass the complexing agent solution into the reactor, and after measuring the ammonia value in the reactor to be 2.5 g / L, pass the alkali solution into the reactor and adjust the pH value in the reactor to 13; at the same time, pass high-purity nitrogen below the liquid level of the reactor at a nitrogen flow rate of 0.3m 3 / h, prepare base solution.

[0157] (3) The mixed salt solution, complexing agent solution and alkali solution in step (1) are added into the reactor in sequence through a precision constant flow pump, and the flow rate of the ammonia solution is adjusted to stabilize the ammonia value at 2.5 g / L. A gradient flow process is performed. The reaction process is divided into four stages:

[0158] ① In the first stage, the feed flow rate of the mixed salt solution is 2L / h, the pH value in the kettle is adjusted to about 12.9, and the thickener is turned on after overflowing for 8h to increase the solid content. The nitrogen inlet flow rate in this stage is 0.3 m 3 / h, reaction time is 15h;

[0159] ② In the second stage, the feed rate of the mixed salt solution was increased to 4 L / h, and the pH value in the kettle gradually decreased to about 12.7. The nitrogen inlet flow rate in this stage was 0.6 m 3 / h, reaction time is 10h;

[0160] ③ In the third stage, the feed rate of the mixed salt solution was further increased to 6 L / h, and the pH value in the kettle gradually decreased to about 12.5. The nitrogen inlet flow rate in this stage was 0.6 m 3 / h, reaction time is 5h;

[0161] ④ In the fourth stage, the feed flow rate of the mixed salt solution is further increased to 8L / h, and the pH value in the kettle is adjusted to about 12. The nitrogen inlet flow rate in this stage is 0.2 m 3 / h, until the particle size of the precipitate reaches about 2.3μm, then the machine is shut down to prepare a mixed slurry.

[0162] (4) The mixed slurry was put into an aging kettle, and then introduced into a centrifuge. The 10 mol / L hot alkali was used as a washing liquid, and the centrifugal washing was performed for 20 min. The hot water was used for centrifugal washing for 40 min to obtain the material to be dried. The material to be dried was placed in a blast drying oven, the drying temperature was 130 °C, and the drying time was 20 h. The dried material was sieved with a 325 mesh screen, and after iron removal, a ternary precursor material with a Zr doping amount of 3000 ppm was obtained.

[0163] Example 2

[0164] The preparation method is similar to that of Example 1, except that in step (1), the concentration of Zr is 0.0012 mol / L, so that the doping amount of Zr in the prepared ternary precursor material is 500 ppm.

[0165] Example 3

[0166] The preparation method is similar to that of Example 1, except that in step (1), the concentration of Zr is 0.012 mol / L, so that the doping amount of Zr in the prepared ternary precursor material is 5000 ppm.

[0167] Example 4

[0168] The preparation method is similar to that of Example 1, except that in step (1), the concentration of Zr is 0.024 mol / L, so that the doping amount of Zr in the prepared ternary precursor material is 10000 ppm.

[0169] Example 5

[0170] The preparation method is similar to that of Example 1, except that in step (1), anhydrous zirconium sulfate is not added to the mixed salt solution (ie, no Zr doping is performed).

[0171] Example 6

[0172] The preparation method is similar to that of Example 1, except that in step (3), the feed flow rate of the mixed salt solution in the four stages is 8 L / h (i.e., high salt solution concentration).

[0173] Example 7

[0174] The preparation method is similar to that of Example 1, except that in step (1), nickel sulfate, cobalt sulfate, manganese sulfate, and zirconium sulfate tetrahydrate are prepared into a mixed salt solution with a total ion concentration of 1.5 mol / L, the concentration of Zr is 0.0073 mol / L, and the Zr doping amount in the finally prepared ternary precursor material is 2500 ppm.

[0175] Example 8

[0176] The preparation method is similar to that of Example 1, except that in step (3), the process of "overflowing for 8 hours" is omitted in the first stage.

[0177] Example 9

[0178] The preparation method is similar to that of Example 1, except that in step (1), an equimolar amount of aluminum sulfate is used instead of anhydrous zirconium sulfate.

[0179] Comparative Example 1

[0180] The preparation method is similar to that of Example 1, except that in step (3), the nitrogen inlet flow rate in the four stages is 0.6 m 3 / h.

[0181] Comparative Example 2

[0182] The preparation method is similar to that of Example 1, except that in step (3), the nitrogen inlet flow rate in the four stages is 0.3 m 3 / h.

[0183] Comparative Example 3

[0184] The preparation method is similar to that of Example 1, except that in step (3), the nitrogen inlet flow rate in the first stage is 0.3 m 3 / h, and the nitrogen inlet flow rate in the second stage is 0.4 m 3 / h, and the nitrogen inlet flow rate in the third stage is 0.5 m 3 / h, and the nitrogen inlet flow rate in the fourth stage is 0.6 m 3 / h.

[0185] The ternary precursor materials prepared in Examples 1 to 9 and Comparative Examples 1 to 3 were subjected to relevant performance tests, and the test results are shown in Table 1 below.

[0186] Among them, the test conditions or test standards for each performance test item are as follows:

[0187] (1) Particle size test

[0188] The particle size of the precursor was measured using a Malvern 3000 particle size analyzer.

[0189] (2) Specific surface area test

[0190] The specific surface area of ​​the precursor was tested by a Microscope Surface Analyzer.

[0191] (3) Roundness test

[0192] The cross-sectional electron microscope image of the precursor is processed by Metis software to obtain the roundness of the precursor, which is the average value of the ratio between the comparative circle diameter of the largest cross section of n precursors and the minimum circumscribed circle diameter of the largest cross section, n≥35.

[0193] (4) Test of doping element content

[0194] The content of doping elements in the precursor was tested by inductively coupled plasma atomic emission spectrometer (ICP).

[0195] (5) Button battery performance test

[0196] The ternary positive electrode material precursor prepared in the above examples and comparative examples is prepared into a positive electrode active material, and the prepared positive electrode active material is applied to a button battery, and the specific steps are as follows:

[0197] The ternary positive electrode material precursors prepared in the above embodiments and comparative examples were respectively mixed with lithium hydroxide in a molar ratio of Li:(Ni+Co+Mn)=1.05, and calcined in an oxygen atmosphere. Specifically, they were first calcined at 750°C for 20 hours, and then calcined at 650°C for 15 hours to prepare the positive electrode active material.

[0198] The positive electrode active material, acetylene black and polyvinylidene fluoride (PVDF) prepared above were mixed and dispersed in a solvent N-methylpyrrolidone in a mass ratio of 94:3:3 to prepare a positive electrode active material layer slurry, which was then coated on the surface of the positive electrode current collector aluminum foil, and after drying, rolling, slitting and tab welding, a positive electrode sheet was obtained, and a Celgard polypropylene separator, a metal lithium sheet and an electrolyte were used to prepare a CR2032 button battery, wherein the electrolyte included lithium hexafluorophosphate, diethyl carbonate and ethylene carbonate, the concentration of lithium hexafluorophosphate was 1 mol / L, and the volume ratio of diethyl carbonate to ethylene carbonate was 1:1. The first charge and discharge specific capacity and capacity retention rate of the CR2032 button battery prepared above were tested under the test conditions of 25°C, 2.5-4.3V and 0.2C:

[0199] (1) Initial charge and discharge specific capacity

[0200] The Xinwei CT-3008W-5V3A-A1 comprehensive battery tester was used, the test temperature was set to 25°C, the voltage was 2.75-4.3V, charging was performed at 0.2C, and discharging was performed at 0.2C to obtain the first charge and discharge specific capacity of the button battery.

[0201] (2) Capacity retention rate

[0202] The capacity retention rate of the button cell was obtained by using a Xinwei CT-3008W-5V3A-A1 comprehensive battery tester, setting the test temperature to 45°C, the voltage to 4.25-3V, the constant voltage cutoff current to 20mA, and cycling for 300 cycles.

[0203] (6) Morphology test

[0204] The ternary precursor material was placed under a scanning electron microscope and cut along the diameter of the particle. The area of ​​the pores in each part and the area of ​​the corresponding parts were counted, and the porosity of a single secondary particle was calculated according to the pore area / corresponding area × 100%. The diameter of the core, the angle and longitudinal depth of the sawtooth, and the length and width of the primary particle can all be measured using Nano Measurer 1.2 software.

[0205] Table 1

[0206]

[0207] Table 2

[0208]

[0209] Table 3

[0210]

[0211] Comparing the examples with the comparative examples, it can be seen that the ternary precursor material prepared by the preparation method of the present application has a small particle size, a high specific surface area and sphericity, and a narrow particle size distribution. Accordingly, the ternary positive electrode material and button battery prepared from the precursor have good discharge specific capacity and cycle performance.

[0212] Figures 1 and 2 are scanning electron microscope images and cross-sectional images of the ternary precursor material prepared in Example 1, respectively. The secondary particles of Example 1 prepared by zirconium doping have uniform particle size distribution, good sphericity, dense primary particle packing, fine surface whiskers of about 80-120 nm, and an aspect ratio of 5-10. The ternary precursor material is divided into an inner core and an outer layer. The inner core includes a loose and porous honeycomb structure formed by the interweaving of primary particles. The inner core has a diameter of 1.0-1.5 μm, accounting for 40%-60% of the diameter of the ternary precursor particles; the outer layer includes a sawtooth structure, the angle between the sawtooths is 1-30°, and the longitudinal depth of a single sawtooth is 200-600 nm. Figure 3 is a cross-sectional EDS-mapping spectrum of the ternary precursor material prepared in Example 1. The doped zirconium element is evenly distributed without obvious regional differences.

[0213] Figure 4 is a scanning electron microscope image of the ternary precursor material prepared in Example 5. Compared with Example 1, the sphericity of the material without Zr doping is poor, the multi-head phenomenon is obvious, there are more small particles, and the particle size distribution is wider, indicating that Zr doping can significantly improve the sphericity and alleviate the fine powder and multi-head phenomenon.

[0214] Figures 5 and 6 are scanning electron microscope images and cross-sectional images of the ternary precursor material prepared in Comparative Example 1. Compared with Example 1, the cross-sectional surface of the ternary precursor material prepared under almost non-oxidizing conditions is dense inside and has a low specific surface area (BET), which is not conducive to the diffusion of active ions into the interior of the precursor.

[0215] Figures 7 and 8 are scanning electron microscope images and cross-sectional images of the ternary precursor material prepared in Comparative Example 2. Compared with Example 1, the interior of the ternary precursor material prepared by over-oxidation is too loose, the BET is too high, and the structure is easy to collapse during sintering, which is not conducive to long-term circulation.

[0216] Figure 9 is a scanning electron microscope image of the ternary precursor material prepared in Example 6. Compared with Example 1, the precursor prepared in the early stage with high salt solution concentration has serious agglomeration, many small particles, poor sphericity, and obvious multi-head phenomenon, while Example 1 prepared by the gradient rising flow process has obviously better sphericity, indicating that the gradient rising flow process is conducive to the improvement of sphericity.

[0217] Example 7: Zirconium sulfate tetrahydrate is mixed with nickel-cobalt-manganese salt solution. Since zirconium sulfate tetrahydrate will hydrolyze to form zirconium dioxide hydrate It is a white flocculent gel that is insoluble in water and will clog the metering pump. At the same time, due to the formation of flocculent gel, the actual doping amount of Zr is low.

[0218] Figure 10 is a scanning electron microscope image of the ternary precursor material prepared in Example 8. Compared with Example 1, full reflux begins when the machine is turned on, and the first stage "overflow 8h" process is omitted. The prepared precursor has poor sphericity and severe agglomeration.

[0219] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0220] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A ternary precursor material, characterized in that: The secondary particles are formed by agglomeration of primary particles, wherein the median particle size D50 of the secondary particles is 2 μm to 3 μm, and the specific surface area of ​​the secondary particles is 12 m 2 / g~25m 2 / g, the roundness of the secondary particles is 0.75-0.99, and the particle size distribution of the secondary particles satisfies: .

2. The ternary precursor material according to claim 1, characterized in that: The secondary particles include an inner core and an outer layer formed on the surface of the inner core, the inner core has a porosity of 15% to 25%, and the outer layer has a porosity of 1% to 15%.

3. The ternary precursor material according to claim 2, characterized in that: The inner core comprises a honeycomb structure formed by the primary particles interweaving with each other; and / or, The outer layer includes a sawtooth structure formed by the primary particles interweaving with each other, and the sawtooth structure includes a plurality of sawteeth extending along the radial direction of the secondary particle from an end relatively close to the inner core to an end relatively far from the inner core.

4. The ternary precursor material according to claim 3, characterized in that: The ratio of the diameter of the inner core to the diameter of the secondary particles is 40% to 65%; And / or, the angle between any two adjacent saw teeth is 1° to 60°; And / or, the longitudinal depth of a single sawtooth is 200nm~600nm; And / or, the primary particles are in the shape of laths.

5. The ternary precursor material according to claim 3 or 4, characterized in that: The diameter of the core is 1 μm to 1.5 μm; And / or, the length of the primary particles is 300nm~800nm; And / or, the width of the primary particle is 50nm~150nm; And / or, the aspect ratio of the primary particles is 2-10.

6. The ternary precursor material according to claim 1 or 2, characterized in that: Satisfy at least one of the following conditions: (1) The ternary precursor material satisfies the following chemical formula: (Ni a Co b Mn c )M d (OH)2, where 0.8 ≤ a < 1.0, 0 < b ≤ 0.1, 0 < c ≤ 0.1, 0 ≤ d ≤ 0.005, M is a doping element and includes at least one of Zr, La, Al, Ce, W, and B; Optionally, the doping element includes Zr; Optionally, the doping element is uniformly distributed in the ternary precursor material; Optionally, in the ternary precursor material, the content of the doping element is 500ppm~5000ppm; (2) The tap density of the ternary precursor material is 1.5 g / cm 3 ~2g / cm 3 .

7. A method for preparing a ternary precursor material, characterized in that: include: Under the condition of continuously introducing nitrogen and maintaining a certain ammonia value, adding a mixed salt solution and a first alkali solution to the base liquid in four stages respectively, so as to successively carry out four stages of co-precipitation reaction to prepare a mixed slurry; wherein, in the four stages, the nitrogen introduction flow rate of the first stage is less than the nitrogen introduction flow rate of the second stage, and the nitrogen introduction flow rate of the third stage is greater than the nitrogen introduction flow rate of the fourth stage; After aging, separating and washing the mixed slurry, the ternary precursor material is prepared, wherein the ternary precursor material comprises secondary particles formed by agglomeration of primary particles, the median particle size D50 of the secondary particles is 2 μm to 3 μm, and the specific surface area of ​​the secondary particles is 12 m 2 / g~25m 2 / g, the roundness of the secondary particles is 0.75-0.99, and the particle size distribution of the secondary particles satisfies: .

8. The preparation method according to claim 5, characterized in that: Satisfy at least one of the following conditions: (1) The ammonia value is 1g / L~10g / L, and can be optionally 2g / L~2.5g / L; (2) The mixed salt solution contains nickel salt, cobalt salt, manganese salt and optional salt of doped metal; Optionally, the doping metal includes at least one of Zr, La, Al, Ce, and W, and may further be Zr; Optionally, when the doping metal is Zr, the concentration of Zr in the mixed salt solution is 0.0012 mol / L to 0.012 mol / L; Optionally, when the doping metal is Zr, the salt of the doping metal includes anhydrous zirconium sulfate; (3) The concentration of the mixed salt solution is 1 mol / L to 2.5 mol / L.

9. The preparation method according to claim 7 or 8, characterized in that: Satisfy at least one of the following conditions: (1) In the four stages, the nitrogen inlet flow rates are respectively: The nitrogen inlet flow rate in the first stage is 0.3m 3 / h~0.4m 3 / h; The nitrogen flow rate of the second stage is 0.5m 3 / h~0.6m 3 / h; The nitrogen inlet flow rate of the third stage is 0.5m 3 / h~0.6m 3 / h; The nitrogen inlet flow rate of the fourth stage is 0.1m 3 / h~0.3m 3 / h; (2) In the four stages, the feed flow rate of the mixed salt solution increases gradually; Optionally, in the first stage, the feed flow rate of the mixed salt solution is 0.1L / h~2L / h; Optionally, in the second stage, the feed flow rate of the mixed salt solution is 2L / h~4L / h; Optionally, in the third stage, the feed flow rate of the mixed salt solution is 4 L / h to 6 L / h; Optionally, in the fourth stage, the feed flow rate of the mixed salt solution is 6L / h~8L / h; (3) Among the four stages, the pH value of the first stage>the pH value of the second stage>the pH value of the third stage>the pH value of the fourth stage; Optionally, 12.9≤the pH value of the first stage≤13.2; Optionally, 12.6<the pH value of the second stage≤12.8; Optionally, 12.4<the pH value of the third stage≤12.6; Optionally, 11.5≤the pH value of the fourth stage≤12.4; (4) in the first stage, causing the mixed salt solution to overflow; Optionally, the overflow time is 8h~10h.

10. A ternary positive electrode material, characterized in that: The ternary precursor material is prepared by the ternary precursor material described in any one of claims 1 to 6 or the ternary precursor material prepared by the preparation method described in any one of claims 7 to 9.

Citation Information

Cited By

  • Monocrystal ternary precursor, positive electrode material and preparation method

    CN118084080A